2015
DOI: 10.3389/fpsyg.2015.00959
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership: application to women leaders

Abstract: The purpose of this perspective article is to present the argument that authentic leadership is a gendered representation of leadership. We first provide a brief history of leadership theories and definitions of authentic leadership. We then critique authentic leadership and offer arguments to support the premise that authentic leadership is not gender-neutral and is especially challenging for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
1
42
1
2
Order By: Relevance
“…Among them, we reinforce the need for comparative longitudinal studies between the level of results achieved by authentic and non-authentic leaders, or, better said, by leaders who may be characterized as more or less authentic. Furthermore, no mentions of gender issues were found in the responses provided by the participating leaders concerning the challenges they face, therefore, it is also suggested that specific research be conducted to investigate whether the criticisms made by Hopkins and O'Neil (2015) can be empirically proven.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, we reinforce the need for comparative longitudinal studies between the level of results achieved by authentic and non-authentic leaders, or, better said, by leaders who may be characterized as more or less authentic. Furthermore, no mentions of gender issues were found in the responses provided by the participating leaders concerning the challenges they face, therefore, it is also suggested that specific research be conducted to investigate whether the criticisms made by Hopkins and O'Neil (2015) can be empirically proven.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the well‐noted double bind dilemma (Eagly & Carli, ; Jamieson, ) can mean women are seen as inauthentic if they do not act in accordance with gender‐normative behaviors. Yet they can be seen as weak leaders if they act authentically feminine (Hopkins & O'Neil, ). Moreover, many women have been socialized away from leader identities, potentially causing them to feel inauthentic when they do take on the power necessary for some leadership roles and behaviors (Ibarra, ).…”
Section: The Four‐fold Model Of Socially Conscious Leadershipmentioning
confidence: 99%
“…Eagly (2005) suggested that women have been a social out-group in leadership for a long time and will be therefore less likely to be respected and to be perceived as authentic in their relations with followers than men. Hopkins and O'Neil (2015) also suggested a perceived mismatch between the attributes stereotypically ascribed to women and attributes inherent in authentic leadership. To date none of these arguments have undergone rigorous empirical testing, which is one purpose of this research.…”
Section: Running Head: Leader Prototypes and Gendermentioning
confidence: 99%
“…Based on these theoretical views and empirical findings we argue that authentic leadership represents a communal leadership style. While for some leadership styles empirical evidence supports that they are positively associated with female leaders (e.g., transformational leadership; Vinkenburg, van Engen, Eagly, & Johannesen-Schmidt, 2011), the relationships between leader prototypes, leader gender, and perceptions of authentic leadership lack rigorous empirical testing (Eagly, 2005;Hopkins & O'Neil, 2015).…”
Section: Running Head: Leader Prototypes and Gender 11mentioning
confidence: 99%